PENGARUH PENGETAHUAN PERPAJAKAN DAN PERSEPSI KEADILAN TERHADAP TINGKAT KEPATUHAN WAJIB PAJAK MELALUI KEPERCAYAAN - Ari Yulianti; Asep Kurniawan (Jurnal Riset Keuangan dan Akuntansi, 2019)
This study aims to determine the effect of tax knowledge and perception of justice to compliance of taxpayer pp 46 year 2013 registered at tax office Subang and to determine the influence of knowledge taxation and perception of justice to compliance of taxpayer pp 46 year 2013 registered at tax office Subang through trust variables. This research uses quantitative descriptive method by using primary data. Data collection technique is by questionnaire. The population in this study is all taxpayers entrepreneurs included into PP 46 year 2013 registered at  Tax Office  Subang, and samples in this study as many as 100 respondents. Hypothesis testing using Structural Equation Modeling (SEM) analysis. The results of this study indicate that tax knowledge have an effect on taxpayer compliance, and perception of justice have an effect on taxpayer compliance, whereas trust does not mediate the influence of tax knowledge on compliance and perception of justice toward compliance.Keywords: Tax Knowledge, Perception of Justice, Trust, Tax Compliance